Wear-resistant high-transparency optical film and method for manufacturing the same
Patent Information
- Application Number
- CN202311742485.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-15
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-12-15
AI Technical Summary
利用二氧化硅纳米颗粒在光学玻璃上沉积的单层薄膜具备接近100%的峰值透射率,然而这种薄膜结构疏松,不耐擦拭,环境适应性较差
[0022] This invention provides a method for preparing a wear-resistant, high-transmittance optical thin film, comprising the following steps: applying a first coating to a substrate surface using zirconia sol, followed by heat treatment to obtain an inner layer film; the zirconia sol comprises zirconia nanoparticles, diethylene glycol, polyvinylpyrrolidone, nitric acid, ethanol, and water; applying a second coating to the inner layer film surface using acid-catalyzed silica sol, followed by annealing to obtain the wear-resistant, high-transmittance optical thin film; the acid-catalyzed silica sol comprises silica, hydrochloric acid, ethanol, and water. This invention employs a chemical liquid-phase film-forming technique, using zirconia sol to deposit the inner layer film and acid-catalyzed silica sol to deposit the outer layer film. The resulting bilayer film system is the wear-resistant, high-transmittance optical thin film of this invention. This optical thin film exhibits excellent abrasion resistance and achieves a peak transmittance of nearly 100%; furthermore, by adjusting the thickness of the inner and outer layers, the transmission peak position of the film can be controlled to meet the anti-reflection requirements of different wavelengths from ultraviolet to near-infrared.
Smart Images

Figure CN117724196B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of optical thin film technology, and in particular to a wear-resistant, high-transmittance optical thin film and its preparation method. Background Technology
[0002] Anti-reflective optical thin films are widely used on the surfaces of various optical lenses to reduce the reflection of incident light and decrease light loss during transmission. Vacuum evaporation is the most common method for modern optical thin film preparation; however, the expensive equipment results in high coating costs. Chemical liquid phase deposition methods offer advantages such as simplicity and low cost, making them suitable for coating optical lenses of various shapes. They are currently used in coating various optical glass surfaces.
[0003] During use, optical lenses are easily contaminated with dust particles, organic oils, and other pollutants, leading to a significant decline in their optical performance. Therefore, cleaning is essential for optical lens surfaces, placing high demands on the durability of the thin films on these surfaces. Single-layer antireflective films deposited on optical glass using silica nanoparticles achieve near-100% peak transmittance; however, these films have a porous structure, are not resistant to abrasion, and have poor environmental adaptability. Using a combination of titanium dioxide and silica to prepare a bilayer antireflective coating on optical glass can improve the coating's durability and achieve better abrasion resistance. However, the high refractive index of titanium dioxide makes it difficult to perfectly match with the low refractive index of silica in a bilayer system, hindering the achievement of near-100% peak transmittance on substrates such as fused silica. Therefore, current optical antireflective coatings struggle to balance abrasion resistance and high transmittance. Summary of the Invention
[0004] In view of this, the present invention provides a wear-resistant, high-transmittance optical thin film and its preparation method. The optical thin film provided by the present invention has both excellent abrasion resistance and can achieve a peak transmittance of nearly 100%.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0006] A method for preparing a wear-resistant and high-transmittance optical thin film includes the following steps:
[0007] A first coating is applied to the substrate surface using zirconia sol, followed by heat treatment to obtain an inner layer film; the zirconia sol comprises zirconia nanoparticles, diethylene glycol, polyvinylpyrrolidone, nitric acid, ethanol, and water;
[0008] A second coating is applied to the surface of the inner layer film using an acid-catalyzed silica sol, followed by annealing to obtain a wear-resistant and high-transmittance optical film. The acid-catalyzed silica sol comprises silica, hydrochloric acid, ethanol, and water.
[0009] Preferably, the method for preparing the zirconium oxide sol includes:
[0010] Diethylene glycol, polyvinylpyrrolidone, a portion of ethanol and zirconium oxide precursor were mixed to obtain the first mixture;
[0011] Nitric acid, water, and the remaining ethanol are mixed to obtain a second mixture;
[0012] The first mixture and the second mixture are mixed and allowed to stand for aging to obtain the zirconium oxide sol.
[0013] Preferably, in the feed solution obtained by mixing the first mixture and the second mixture: the concentration of the zirconium oxide precursor is 0.2-0.3 mol / L, the molar ratio of diethylene glycol to zirconium oxide precursor is (1-2):1, the molar ratio of water to zirconium oxide precursor is (1-2):1, the mass fraction of polyvinylpyrrolidone is 10%-15%, and the mass fraction of nitric acid is 0.05%-0.15%; the zirconium oxide precursor is zirconium propoxide.
[0014] Preferably, the method for preparing the acid-catalyzed silica sol includes:
[0015] Ethanol, water, hydrochloric acid and silica precursor were mixed and allowed to stand for aging to obtain the acid-catalyzed silica sol.
[0016] The molar ratio of ethanol, water, hydrochloric acid and silica precursor is (37-38):(2-3):(0.003-0.004):1; the silica precursor is tetraethyl orthosilicate.
[0017] Preferably, the first coating and the second coating are applied by dip-coating; the heat treatment temperature is 150–400°C and the holding time is 30 min or more; the annealing temperature is 400–700°C and the holding time is 1 h or more.
[0018] Preferably, the substrate is a fused silica substrate.
[0019] Preferably, before the first coating, the substrate is further subjected to pretreatment; the pretreatment includes the following steps: ultrasonically cleaning the substrate sequentially in an alkaline cleaning solution and pure water, and then slowly lifting and dehydrating it in hot water; the lifting speed of the slow lifting and dehydrating is 0.5 to 1.5 mm / s, and the temperature of the hot water is 45 to 60°C.
[0020] The present invention also provides a wear-resistant and high-transmittance optical thin film prepared by the preparation method described above, comprising an inner layer film and an outer layer film disposed on the surface of the inner layer film, wherein the inner layer film is in contact with a substrate; the inner layer film is a zirconium oxide film and the outer layer film is a silicon dioxide film.
[0021] Preferably, the thickness of the inner layer film is 58–175 nm, and the thickness of the outer layer film is 69–209 nm.
[0022] This invention provides a method for preparing a wear-resistant, high-transmittance optical thin film, comprising the following steps: applying a first coating to a substrate surface using zirconia sol, followed by heat treatment to obtain an inner layer film; the zirconia sol comprises zirconia nanoparticles, diethylene glycol, polyvinylpyrrolidone, nitric acid, ethanol, and water; applying a second coating to the inner layer film surface using acid-catalyzed silica sol, followed by annealing to obtain the wear-resistant, high-transmittance optical thin film; the acid-catalyzed silica sol comprises silica, hydrochloric acid, ethanol, and water. This invention employs a chemical liquid-phase film-forming technique, using zirconia sol to deposit the inner layer film and acid-catalyzed silica sol to deposit the outer layer film. The resulting bilayer film system is the wear-resistant, high-transmittance optical thin film of this invention. This optical thin film exhibits excellent abrasion resistance and achieves a peak transmittance of nearly 100%; furthermore, by adjusting the thickness of the inner and outer layers, the transmission peak position of the film can be controlled to meet the anti-reflection requirements of different wavelengths from ultraviolet to near-infrared.
[0023] In summary, the method of the present invention can prepare antireflective films with peak transmittance of nearly 100% in the ultraviolet to near-infrared bands on a substrate, and the films have excellent abrasion resistance, which greatly improves the environmental adaptability of the film while ensuring the spectral performance of the film. Attached Figure Description
[0024] Figure 1 This is a process flow diagram for preparing the wear-resistant and high-transmittance optical thin film according to the present invention. Detailed Implementation
[0025] This invention provides a method for preparing a wear-resistant and high-transmittance optical thin film, comprising the following steps:
[0026] A first coating is applied to the substrate surface using zirconia sol, followed by heat treatment to obtain an inner layer film; the zirconia sol comprises zirconia nanoparticles, diethylene glycol, polyvinylpyrrolidone, nitric acid, ethanol, and water;
[0027] A second coating is applied to the surface of the inner layer film using an acid-catalyzed silica sol, followed by annealing to obtain a wear-resistant and high-transmittance optical film. The acid-catalyzed silica sol comprises silica, hydrochloric acid, ethanol, and water.
[0028] The process flow diagram for preparing wear-resistant and high-transmittance optical thin films according to this invention is as follows: Figure 1 As shown below, in conjunction with Figure 1 Please provide a detailed explanation.
[0029] This invention employs a zirconium oxide sol to form a first coating on a substrate surface, followed by heat treatment to obtain an inner layer film. In this invention, the substrate is preferably a fused silica substrate; prior to the first coating, the substrate is preferably pretreated; the pretreatment preferably includes the following steps: ultrasonically cleaning the substrate sequentially in an alkaline cleaning solution and then in pure water, followed by slow-speed lifting dehydration drying in hot water; the lifting speed for the slow-speed lifting dehydration drying is preferably 0.5–1.5 mm / s, more preferably 1 mm / s, and the temperature of the hot water is preferably 45–60°C, more preferably 50°C; the alkaline cleaning solution is preferably a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is preferably 1–10 wt%, more preferably 2–8 wt%; the ultrasonic frequency for ultrasonic cleaning in the sodium hydroxide solution is preferably 40 kHz, the power density is preferably 10 W / L, and the cleaning time is preferably 10 min; the ultrasonic frequency for ultrasonic cleaning in pure water is preferably 40 kHz, the power density is preferably 10 W / L, and the cleaning time is preferably 10 min.
[0030] In this invention, the zirconium oxide sol preferably comprises zirconium oxide nanoparticles, diethylene glycol, polyvinylpyrrolidone, nitric acid, ethanol and water, wherein nitric acid is a catalyst, diethylene glycol is a complexing agent, and polyvinylpyrrolidone plays a surface modification role.
[0031] In this invention, the preferred method for preparing the zirconia sol includes: mixing diethylene glycol, polyvinylpyrrolidone, a portion of ethanol, and a zirconia precursor to obtain a first mixture; mixing nitric acid, water, and the remaining portion of ethanol to obtain a second mixture; and mixing the first and second mixtures and allowing them to stand for aging to obtain the zirconia sol. When preparing the first mixture, this invention preferably mixes diethylene glycol, polyvinylpyrrolidone, and a portion of ethanol first, then adds zirconium propoxide, seals the mixture, and stirs for 30 minutes to obtain the first mixture. When preparing the second mixture, this invention preferably mixes nitric acid, water, and the remaining portion of ethanol, seals the mixture, and stirs for 30 minutes to obtain the second mixture. After obtaining the first and second mixtures, this invention preferably rapidly mixes the first and second mixtures under vigorous stirring conditions, then seals and stirs for 60 minutes; the preferred stirring speed is 300–1000 rpm. This invention does not have special requirements for the ratio of a portion of ethanol to the remaining portion of ethanol, as long as it achieves uniform dispersion and dissolution of each component. In this invention, the static aging time is preferably 15 to 20 days, and the static aging temperature is preferably 20 to 30°C, more preferably 25°C.
[0032] In this invention, the concentration of the zirconium oxide precursor in the mixture obtained by mixing the first mixture and the second mixture is preferably 0.2-0.3 mol / L, more preferably 0.28 mol / L; the molar ratio of diethylene glycol to zirconium oxide precursor is preferably (1-2):1, more preferably 2:1; the molar ratio of water to zirconium oxide precursor is preferably (1-2):1, more preferably 2:1; the mass fraction of polyvinylpyrrolidone is preferably 10%-15%, more preferably 12%-15%; and the mass fraction of nitric acid is preferably 0.05%-0.15%, more preferably 0.1%; the zirconium oxide precursor is preferably zirconium propoxide.
[0033] In this invention, the method for coating the first film is preferably the dip-coating method; this invention does not have special requirements for the dipping speed of the dip-coating method, but in specific embodiments of this invention, the dipping speed can be adjusted according to the requirements for film thickness.
[0034] After the first coating is completed, the substrate with the inner layer wet film on its surface is subjected to heat treatment. The heat treatment temperature is preferably 150–400°C, more preferably 200–400°C, the heating rate to the heat treatment temperature is preferably 10°C / min, and the holding time for the heat treatment is preferably 30 min or more, more preferably 30–60 min. The heat treatment is preferably carried out in a muffle furnace. This invention evaporates the solvent and decomposes organic additives and organic groups through heat treatment. After the heat treatment, the substrate with the inner layer film is preferably allowed to cool naturally to room temperature before the subsequent second coating is applied.
[0035] After obtaining the inner layer film, the present invention uses an acid-catalyzed silica sol to apply a second coating to the surface of the inner layer film, followed by annealing to obtain a wear-resistant and high-transmittance optical thin film. In the present invention, the acid-catalyzed silica sol comprises silica, hydrochloric acid, ethanol, and water; the ethanol is preferably anhydrous ethanol.
[0036] In this invention, the preferred method for preparing the acid-catalyzed silica sol includes: mixing ethanol, water, hydrochloric acid, and a silica precursor, followed by static aging to obtain the acid-catalyzed silica sol. The preferred molar ratio of ethanol, water, hydrochloric acid, and the silica precursor is (37-38):(2-3):(0.003-0.004):1, more preferably 37.39:2.87:0.00385:1; the preferred silica precursor is tetraethyl orthosilicate; the preferred method for mixing the ethanol, water, hydrochloric acid, and silica precursor is: sequentially adding ethanol, water, hydrochloric acid, and tetraethyl orthosilicate to a container, followed by stirring at 20-30°C for 10 minutes; the preferred aging temperature is 20-30°C, more preferably 25°C, and the preferred aging time is 3 days.
[0037] In this invention, the second coating method is preferably the dip-coating method, specifically, the substrate with the inner layer film is dipped and pulled in an acid-catalyzed silica sol to form an outer layer wet film on the surface of the inner layer film. This invention does not have special requirements for the dipping speed of the dip-coating method. In specific embodiments of this invention, the dipping speed can be adjusted according to the requirements for film thickness.
[0038] After the second coating is completed, the substrate with the outer wet film is subjected to annealing treatment. The annealing temperature is preferably 400-700℃, more preferably 500-700℃, the heating rate to the heat treatment temperature is preferably 10℃ / min, and the holding time of the annealing treatment is preferably 1 hour or more, more preferably 1-2 hours. The annealing treatment is preferably carried out in a muffle furnace. The present invention uses annealing to evaporate the solvent and simultaneously decompose the ethoxy (-OC2H5) organic groups.
[0039] This invention also provides a wear-resistant, high-transmittance optical film prepared by the method described above, comprising an inner layer film and an outer layer film disposed on the surface of the inner layer film, wherein the inner layer film is in contact with a substrate; the inner layer film is a zirconium oxide film, specifically formed from zirconium oxide nanoparticles, and the outer layer film is a silicon dioxide film, specifically formed from silicon dioxide nanoparticles. In this invention, by adjusting the thickness of the inner and outer layer films, an antireflective film with a peak transmittance close to 100% from the ultraviolet to near-infrared bands can be obtained. For example, increasing the thickness of the inner and outer layer films shifts the transmission peak position to longer wavelengths. The thickness of the inner and outer layer films is achieved by changing the lifting speed of the immersion and lifting process. In a specific embodiment of this invention, the peak transmittance of the wear-resistant, high-transmittance optical film is above 99.5%.
[0040] In this invention, the thickness of the inner layer film is preferably 58-175 nm, and the thickness of the outer layer film is preferably 69-209 nm. Adjusting the thickness of the inner and outer layers within the above ranges enables the obtained wear-resistant and high-transmittance optical film to achieve enhanced transmittance in the wavelength range of 400-1200 nm.
[0041] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0042] Example 1
[0043] The fused silica substrate was ultrasonically cleaned in a 10 wt% sodium hydroxide solution for 10 min at a frequency of 40 kHz and a power density of 10 W / L. Then it was ultrasonically rinsed in pure water for 10 min at a frequency of 40 kHz and a power density of 10 W / L. Finally, it was slowly lifted and dried in 50°C hot water at a speed of 1 mm / s.
[0044] Preparation of zirconia sol: Diethylene glycol, polyvinylpyrrolidone, and ethanol were mixed, and then zirconium propoxide was added. The mixture was stirred in a sealed container for 30 min to obtain the first mixture. Nitric acid, pure water, and ethanol were mixed and stirred in a sealed container for 30 min to obtain the second mixture. Under vigorous stirring, the first and second mixtures were rapidly mixed and then stirred in a sealed container for 60 min. After that, the mixture was allowed to stand at room temperature for 15 days to obtain zirconia sol. The concentration of zirconium propoxide in the obtained zirconia sol was 0.28 mol / L, the molar ratio of diethylene glycol to zirconium propoxide was 2:1, the molar ratio of water to zirconium propoxide was 2:1, the polyvinylpyrrolidone content was 15%, and the nitric acid content was 0.1%.
[0045] Preparation of acid-catalyzed silica sol: Anhydrous ethanol, water, hydrochloric acid, and tetraethyl orthosilicate were mixed in a molar ratio of 37.39:2.87:3.85×10⁻⁶. -3 The solutions were added sequentially to the reaction vessel at a ratio of 1.00, stirred at room temperature for 10 minutes, and then sealed and stored at room temperature for 3 days to obtain acid-catalyzed silica sol.
[0046] The cleaned fused silica substrate was immersed in zirconium oxide sol and lifted out at a speed of 60 mm / min using the dip-pull method. The sample was then placed in a muffle furnace and heated to 400°C at a heating rate of 10°C / min, held for 1 hour, and then allowed to cool to room temperature. Next, the sample was immersed in acid-catalyzed silica sol and lifted out at a speed of 270 mm / min. The sample was then placed in a muffle furnace and heated to 700°C at a heating rate of 10°C / min, held for 1 hour, and then allowed to cool to room temperature. The resulting film had a transmission peak at 473 nm and a peak transmittance of 99.85%.
[0047] Abrasion resistance test: The film surface was rubbed with an eraser 40 times (20 back-and-forth strokes). No scratches appeared, and the spectrum showed no shift, meeting the severity level 3 requirements of GB / T 26331-2010 "Environmental Adaptability Test Methods for Optical Thin Film Components". After the tape was firmly adhered to the lens surface and quickly pulled off, this was repeated 10 times. No peeling occurred, and the spectrum showed no shift.
[0048] Example 2
[0049] The cleaning process of the fused silica substrate, the preparation of the zirconium oxide sol, and the preparation process of the acid-catalyzed silica sol are the same as in Example 1.
[0050] The cleaned substrate was immersed in zirconia sol and lifted using a dip-coating method at a speed of 60 mm / min. The sample was then placed in a muffle furnace and heated to 400°C at a heating rate of 10°C / min, held at that temperature for 1 hour, and then allowed to cool naturally to room temperature. The sample was then immersed in acid-catalyzed silica sol and lifted at a speed of 250 mm / min. The sample was then placed in a muffle furnace and heated to 400°C at a heating rate of 10°C / min, held at that temperature for 1 hour, and then allowed to cool naturally to room temperature. The resulting film had a transmission peak at 535 nm and a peak transmittance of 99.83%.
[0051] Abrasion resistance test: The film surface was rubbed with an eraser 40 times (20 back-and-forth strokes). No scratches appeared, and the spectrum showed no shift, meeting the severity level 3 requirements of GB / T 26331-2010 "Environmental Adaptability Test Methods for Optical Thin Film Components". After the tape was firmly adhered to the lens surface and quickly pulled off, this was repeated 10 times. No peeling occurred, and the spectrum showed no shift.
[0052] Example 3
[0053] The cleaning process of the fused silica substrate, the preparation of the zirconium oxide sol, and the preparation process of the acid-catalyzed silica sol are the same as in Example 1.
[0054] The cleaned substrate was immersed in zirconia sol and lifted out at a speed of 60 mm / min using the dip-coating method. The sample was then placed in a muffle furnace and heated to 200°C at a heating rate of 10°C / min, held at that temperature for 1 hour, and then allowed to cool naturally to room temperature. The sample was then immersed in acid-catalyzed silica sol and lifted out at a speed of 200 mm / min. The sample was then placed in a muffle furnace and heated to 700°C at a heating rate of 10°C / min, held at that temperature for 1 hour, and then allowed to cool naturally to room temperature. The resulting film had a transmission peak at 381 nm and a peak transmittance of 99.53%.
[0055] Abrasion resistance test: The film surface was rubbed with an eraser 40 times (20 back-and-forth strokes). No scratches appeared, and the spectrum showed no shift, meeting the severity level 3 requirements of GB / T 26331-2010 "Environmental Adaptability Test Methods for Optical Thin Film Components". After the tape was firmly adhered to the lens surface and quickly pulled off, this was repeated 10 times. No peeling occurred, and the spectrum showed no shift.
[0056] Example 4
[0057] The cleaning process of the fused silica substrate, the preparation of the zirconium oxide sol, and the preparation process of the acid-catalyzed silica sol are the same as in Example 1.
[0058] The cleaned substrate was immersed in zirconia sol and lifted out at a speed of 100 mm / min using the dip-coating method. The sample was then placed in a muffle furnace and heated to 200°C at a heating rate of 10°C / min, held at that temperature for 1 hour, and then allowed to cool naturally to room temperature. The sample was then immersed in acid-catalyzed silica sol and lifted out at a speed of 400 mm / min. The sample was then placed in a muffle furnace and heated to 400°C at a heating rate of 10°C / min, held at that temperature for 1 hour, and then allowed to cool naturally to room temperature. The resulting film had a transmission peak at 805 nm and a peak transmittance of 99.91%.
[0059] Abrasion resistance test: The film surface was rubbed with an eraser 40 times (20 back-and-forth strokes). No scratches appeared, and the spectrum showed no shift, meeting the severity level 3 requirements of GB / T 26331-2010 "Environmental Adaptability Test Methods for Optical Thin Film Components". After the tape was firmly adhered to the lens surface and quickly pulled off, this was repeated 10 times. No peeling occurred, and the spectrum showed no shift.
[0060] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a wear-resistant, high-transmittance optical thin film, characterized in that, Includes the following steps: A first coating is applied to the substrate surface using zirconia sol, followed by heat treatment to obtain an inner layer film; the zirconia sol comprises zirconia nanoparticles, diethylene glycol, polyvinylpyrrolidone, nitric acid, ethanol, and water; A second coating is applied to the surface of the inner layer film using an acid-catalyzed silica sol, followed by annealing to obtain a wear-resistant and high-transmittance optical film. The acid-catalyzed silica sol comprises silica, hydrochloric acid, ethanol, and water. The method for preparing the zirconium oxide sol includes: Diethylene glycol, polyvinylpyrrolidone, a portion of ethanol and zirconium oxide precursor were mixed to obtain the first mixture; Nitric acid, water, and the remaining ethanol are mixed to obtain a second mixture; The first mixture and the second mixture are mixed and allowed to stand for aging to obtain the zirconium oxide sol; In the feed solution obtained by mixing the first mixture and the second mixture: the concentration of the zirconium oxide precursor is 0.2~0.3 mol / L, the molar ratio of diethylene glycol to zirconium oxide precursor is (1~2):1, the molar ratio of water to zirconium oxide precursor is (1~2):1, the mass fraction of polyvinylpyrrolidone is 10%~15%, and the mass fraction of nitric acid is 0.05%~0.15%; the zirconium oxide precursor is zirconium propoxide. The heat treatment temperature is 150~400℃ and the holding time is more than 30 minutes; the annealing temperature is 400~700℃ and the holding time is more than 1 hour.
2. The preparation method according to claim 1, characterized in that, The method for preparing the acid-catalyzed silica sol includes: Ethanol, water, hydrochloric acid and silica precursor were mixed and allowed to stand for aging to obtain the acid-catalyzed silica sol.
3. The preparation method according to claim 2, characterized in that, The molar ratio of ethanol, water, hydrochloric acid and silica precursor is (37~38):(2~3):(0.003~0.004):1; the silica precursor is tetraethyl orthosilicate.
4. The preparation method according to claim 1, characterized in that, The first coating and the second coating are applied using the dip-coating method.
5. The preparation method according to claim 1, characterized in that, The substrate is a fused silica substrate.
6. The preparation method according to claim 1, characterized in that, Before the first coating, the substrate is further subjected to pretreatment; the pretreatment includes the following steps: ultrasonically cleaning the substrate in an alkaline cleaning solution and pure water in sequence, and then slowly lifting and dehydrating it in hot water; the lifting speed of the slow lifting and dehydrating is 0.5~1.5mm / s, and the temperature of the hot water is 45~60℃.
7. The wear-resistant and high-transmittance optical thin film prepared by the preparation method according to any one of claims 1 to 6, comprising an inner layer film and an outer layer film disposed on the surface of the inner layer film, wherein the inner layer film is in contact with a substrate; the inner layer film is a zirconium oxide film and the outer layer film is a silicon dioxide film.
8. The wear-resistant and high-transmittance optical film according to claim 7, characterized in that, The thickness of the inner layer film is 58~175nm, and the thickness of the outer layer film is 69~209nm.